The role of proprotein convertase subtilisin/kexin 9 (PCSK9) in macrophage activation: a focus on its LDL receptor-independent mechanisms - Katsuki, Shunsuke; Jha, Prabhash Kumar; Aikawa, Elena; Aikawa, Masanori (Frontiers in Cardiovascular Medicine, 2024)
Recent clinical trials demonstrated that proprotein convertase subtilisin/kexin 9 (PCSK9) inhibitors reduce cardiovascular events without affecting systemic inflammation in the patients with coronary artery disease, as determined by high sensitivity C-reactive protein (CRP) levels. However, its pro-inflammatory effects in cardiovascular disease in humans and experimental animals beyond the traditional cholesterol receptor-dependent lipid metabolism have also called attention of the scientific community. PCSK9 may target receptors associated with inflammation other than the low-density lipoprotein <sans-serif>receptor (</sans-serif>LDLR) and members of the LDLR family. Accumulating evidence suggests that PCSK9 promotes macrophage activation not only via lipid-dependent mechanisms, but also lipid-independent and LDLR-dependent or -independent mechanisms. In addition to dyslipidemia, PCSK9 may thus be a potential therapeutic target for various pro-inflammatory diseases.